2019
DOI: 10.1093/ofid/ofz317
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis Reactivates Latent Epstein-Barr Virus Reservoir via Toll-Like Receptor 2 and B-Cell Receptor Activation

Abstract: Latent Epstein-Barr virus (EBV) infection can clinically reactivate in immunosuppressed individuals causing lymphoproliferative disease and rarely hepatitis. In this study, we provide in vivo and in vitro evidence that Treponema pallidum infection can cause EBV reactivation with hepatitis in an immunocompetent patient. We report the diagnostic challenges and immunological findings of coinciding syphilis and EBV-associated hepatitis. Using an in vitro EBV-reactivation assay, we demonstrate that T pallidum react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
(10 reference statements)
0
13
0
Order By: Relevance
“…Similarly, previous studies suggest that HIV-1, HPV, HHV-6, Plasmodium falciparum, Leptospirosis, and Group A Streptococci stimulate EBV reactivation [183][184][185][186][187][188]. In the case of EBV, it was also highlighted that the lytic cycle can be induced by Treponema pallidum through TLR2 and B-cell receptor (BCR) activation [189]. The increased number of antigens or decreased level of circulating antibodies are also likely to trigger EBV reactivation in memory B-cells through BCR [190].…”
Section: Virus Reactivationmentioning
confidence: 70%
“…Similarly, previous studies suggest that HIV-1, HPV, HHV-6, Plasmodium falciparum, Leptospirosis, and Group A Streptococci stimulate EBV reactivation [183][184][185][186][187][188]. In the case of EBV, it was also highlighted that the lytic cycle can be induced by Treponema pallidum through TLR2 and B-cell receptor (BCR) activation [189]. The increased number of antigens or decreased level of circulating antibodies are also likely to trigger EBV reactivation in memory B-cells through BCR [190].…”
Section: Virus Reactivationmentioning
confidence: 70%
“… Artificial stimulation triggers reactivation? 1/2 Cell surface; Diacyl lipopeptides (Pam3CSK4) Activated – EBV [ 21 , 26 ] No – KSHV[ 35 ] Yes – EBV [ 44 , 45 ] Yes – KSHV [ 62 ] Yes – MHV68 in vivo [ 15 ] No – EBV [ 31 ] No – EBV [ 39 ] Yes – EBV [ 67 , 68 ] Minor effect – MHV68 in cells [ 34 ] Yes – MHV68 in cells [ 42 ] 2/6 Cell surface; Triacyl lipopeptides(FSL-1) Activated – EBV [ 21 , 26 ] No – KSHV[ 35 ] Yes – EBV [ 44 , 45 ] Yes – KSHV [ 62 ] Yes – MHV68 in vivo [ 15 ] Minor effect – MHV68 in cells [ 34 ] No – EBV [ 39 ] Yes – EBV [ 67 , 68 ] Yes – MHV68 in cells [ 42 ] No – higher—MHV68 in vivo [ 15 ] 3 Endosome; dsRNA (polyI:C) …”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, another group found that TLR3 activation directly increases RTA expression in a transfection setting [ 66 ], suggesting other TLRs may induce KSHV lytic reactivation in other conditions. In the case of EBV, virus reactivation and EBV-linked hepatitis were reported in a patient with infection with the syphilis pathogen Treponema pallidum, a known inducer of TLR2 [ 67 ]. In addition, stimulation of multiple TLRs can induce expression of the lytic regulator ZEBRA in EBV latently infected cell lines [ 68 ].…”
Section: Tlr Signaling As a Trigger For Lytic Reactivation Of γ-Herpesvirusesmentioning
confidence: 99%
“…It has recently been described that T pallidum infection can cause EBV reactivation with hepatitis in an immunocompetent patient 14 . The authors proved using in vitro EBV reactivation assay that T pallidum reactivated EBV in a Toll‐like receptor 2/B‐cell receptor signaling dependent manner, suggesting that EBV‐associated reactivation or lymphoproliferation should be considered in infections with pathogens that activate TLR2, like T pallidum 14 . In our case, we excluded this possibility with a negative EBV‐IgM serology and the negativity of in situ hybridization for EBV in the liver biopsy.…”
Section: Discussionmentioning
confidence: 99%